Hydrothermal liquefaction of lignocellulosic biomass feedstock to produce biofuels: Parametric study and products characterization. (1st July 2020) - Mathanker, Ankit; Pudasainee, Deepak; Kumar, Amit; Gupta, Rajender
Graphical abstract: Abstract: In this work, hydrothermal liquefaction (HTL) of corn stover, obtained from north Alberta farms, was performed at different temperatures of 250, 300, 350 and 375 °C, initial pressures (Pi ) of 300 and 600 psi and retention time (tr ) of 0, 15, 30 and 60 min. All experiments were performed in a 250 mL autoclave reactor with 5 g corn stover and 30 mL de-ionized water (corresponding feed to water ratio of 1:6) in inert N2 condition. The highest yield of heavy oil (29.25 wt%) was obtained at 300 °C, final pressure (Pf ) of 2200 psi and 0 min retention time. The highest yield of hydrochar (30.21 wt%) was obtained at 350 °C, Pf of 3150 psi and tr of 15 min. Based on elemental analysis and energy calculation, highest carbon content and higher heating value for heavy oil was 76.32 wt% and 35.13 MJ/kg at 375 °C, Pf of 600 psi and tr of 15 min; and for hydrochar it was 68.23 wt% and 24.7 MJ/kg at 350 °C, Pf of 3150 psi and tr of 15 min. The GC–MS results for heavy oil indicated that majority of the compounds were phenolic in nature. SEM and FTIR results confirmed the presence of oxygen containing function groups on hydrochar surface. The gas was mainly composed of CO2, CH4, C2 H6, C2 H4, C3 H6, C4 H8, C4 H6, C5 H12, C6 H14, and C6 H12 .